2014
DOI: 10.1002/nur.21593
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta‐Analysis of Incontinence‐Associated Dermatitis, Incontinence, and Moisture as Risk Factors for Pressure Ulcer Development

Abstract: The aim of this analysis was to identify the association between incontinence-associated dermatitis (IAD), its most important etiologic factors (incontinence and moisture), and pressure ulcers (PUs). A systematic review and meta-analysis were performed. We searched Medline, Embase, CINAHL, Web of Science, and the Cochrane Library for relevant papers dating through March 15, 2013. Fifty-eight studies were included. Measures of relative effect at the univariate level were meta-analyzed. In most studies (86%), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
103
1
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(131 citation statements)
references
References 103 publications
3
103
1
14
Order By: Relevance
“…According to Coleman et al (2013), moisture was indentified as a statistically significant factor in pressure ulcer prediction in 48% of the studies analysed. Using meta-analysis, Beeckman et al (2014) found a possible relationship between incontinence-associated dermatitis and moisture as significant factors for pressure ulcer development. In our study moisture was rated the fourth most significant risk factor, and nurses drew attention to its significance, also choosing excretions as the most frequently present risk factor in pressure ulcer development.…”
Section: Discussionmentioning
confidence: 99%
“…According to Coleman et al (2013), moisture was indentified as a statistically significant factor in pressure ulcer prediction in 48% of the studies analysed. Using meta-analysis, Beeckman et al (2014) found a possible relationship between incontinence-associated dermatitis and moisture as significant factors for pressure ulcer development. In our study moisture was rated the fourth most significant risk factor, and nurses drew attention to its significance, also choosing excretions as the most frequently present risk factor in pressure ulcer development.…”
Section: Discussionmentioning
confidence: 99%
“…Trata-se de uma condição bastante frequente, tendo em conta que existe uma percentagem significativa de pessoas, maioritariamente com 65 e mais anos de idade, internadas em cuidados agudos ou de longa duração, que sofrem de incontinência urinária e/ou fecal (1) . Tipicamente é reconhecida como uma inflamação da superfície da pele caracterizada por vermelhidão (rush cutâneo), que afeta principalmente a região das coxas, nádegas e escroto, em pessoas do sexo masculino e os grandes lábios em mulheres (2,3) . Este tipo de lesão traduz a reação da pele perante o agente agressor, comprometendo de imediato a sua capacidade de atuar como barreira protetora (4) .…”
Section: Introductionunclassified
“…Este tipo de lesão traduz a reação da pele perante o agente agressor, comprometendo de imediato a sua capacidade de atuar como barreira protetora (4) . Se a DAI não for identificada e tratada atempadamente, este rubor e/ou rush cutâneo poderá evoluir rapidamente para a formação local de escoriações e de lesões vesiculares, que com a exposição prolongada aos fatores de risco poderão desencadear um processo infecioso com elevada gravidade (2) . Inicia-se, assim, um ciclo onde se constata um aumento progressivo da inflamação local e de perda de integridade cutânea (1) .…”
Section: Introductionunclassified
“…Scientific sources [2,3] state that pressure ulcers develop more often in elderly patients or the patients who are confined to a chair or a bed, especially moisture and enuresis, as one of etiological factors, which accelerates skin damage and the appearance of pressure ulcers [3]. In European countries, according to one-time research, the risk of development of Stage I-IV pressure ulcers among different age groups accounts for 18.1%.…”
Section: Introductionmentioning
confidence: 99%
“…In European countries, according to one-time research, the risk of development of Stage I-IV pressure ulcers among different age groups accounts for 18.1%. Sacrum and heels are most often affected areas of skin [3,4], in Canada they constitute from 15.8% to 28.2% [5], prevalence of pressure ulcers in Lithuania ranges between 2.7 and 29.5% of all the hospitalized patients [6]. It is necessary to use pressure ulcer preventative measures during all the stages of providing nursing services because they reduce the risk of pressure ulcer development by more than fivefold [6].…”
Section: Introductionmentioning
confidence: 99%